A Critical Analysis of the Philippine Construction Industry: Current Trends, Forecast, and Business Focus for Engineering Design Firms - Siman, Bennegreg Pamplona (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The construction industry in the Philippines plays a vital role in the country's economic growth, infrastructure development, and job creation. The construction industry continues to be one of the predominant drivers of Philippines' economic progress. In 2022, an annual growth rate of 9.2% was obtained by the Philippine construction industry and continues to escalate brought by the flagship project of the former President Rodrigo Duterte, Build! Build! Build! Program (BBB). The current government plans to modernize the country’s infrastructure backbone, increasing construction jobs to maintain rapid growth, captivate investments and expand economic opportunities for all Filipinos. It is globally known that the construction industry regularly consumes more raw materials, resulting in scarcity with our natural resources and produced environmental implications. Therefore, the current engineering and construction industry moves towards green construction and buildings. The Philippine government has been actively promoting infrastructure development as a key driver of economic growth. The country will be the fastest growing construction market with an estimated six percent growth per annum, over the next 15 years. This study provided information on the current trends in the Philippine construction industry, forecasts its trajectory over the next five years, and highlights the necessary business focus for engineering design firms. Information obtained from the literature, project documents, memos, reports, and other data available served as primary inputs for discussion and basis for conclusions and recommendations.